Application Of Inventory And Sales Accounting Information Systems At Ud. Dekrafman Of Pogalan District, Trenggalek District: information systems, accounting, inventory, sales - eki hari iskandar; Syafrudin Arif Marah Manunggal (Jurnal Penelitian Ekonomi dan Akuntansi (JPENSI), 2023)
This study aims to analyze the Application of Inventory and Sales Accounting Information Systems at Ud. Dekrafman of Pogalan District, Trenggalek Regency. The data used in this study were obtained by means of observation, interviews and documentation. The data analysis technique used by researchers in this study is the Credibility Test, Transferability, Dependability, and Confirmability Testing. In this research, the focus under study is the implementation of inventory and sales of the business. The data from the results of this application are then compared with the views of experts, from existing materials and so on. The results of research at UD. So far, Dekrafman has not designed an accounting information system that utilizes technology and only performs a simple recording system, namely a system of cash receipts, cash disbursements and sales, so changes must be made by designing a computerized accounting information system and a manual accounting information system so that it can be more efficient. both in the implementation of financial activities. UD. Dekrafman in overcoming difficulties in compiling financial reports must start designing by designing a computerized and manual accounting information system that is recommende